A new species of Muraenichthys (Anguilliformes: Ophichthidae) from Taiwan, with redescription of Muraenichthys thompsoni Jordan & Richardson, 1908 - Hibino, Yusuke; Ho, Hsuan-Ching; Mccosker, John E. (Zootaxa, 2019)
Muraenichthys longirostris sp. nov. is described based on a single specimen 206 mm total length (TL) collected from off Dong-gang, southwestern Taiwan. The species is characterized by a long and slender snout (18% of head length), unique within the genus. It is also characterized by its position of the dorsal-fin origin (positioned at 2/5 of trunk; horizontal distance from the origin to a vertical through mid-anus 113% of head length), long tail (67% TL), and vertebrae 23-41-131. In addition, Muraenichthys thompsoni Jordan & Richardson, 1908 is redescribed based on the holotype and 63 specimens from Fiji to Madagascar, north to Japan. Muraenichthys malabonensis Herre, 1923 is recognized as a junior synonym of M. thompsoni.